Examining the Relationship between High School Students' Lifelong Learning Tendencies and Problem Solving Self-Appraisal - Gülay Öngel; Erkan Tabancalı (Foxton Books, 2022)
Lifelong learning, which is an uninterrupted learning approach, means that individuals learn to adapt to changing social, cultural, technological, or economic conditions, and thus advance their lives. Educating individuals as lifelong learners for their equal participation in society is an important educational ideal. For these reasons, it is important to investigate the variables that will facilitate individuals to adopt lifelong learning. The study aimed to reveal experimental results about how positive self-appraisal in problem solving will create a motivation on lifelong learning tendency. In this study conducted on high school students, it was first examined whether the change in perceptions of problem solving and lifelong learning differed according to gender, and then the relationship between these two variables was aimed to be revealed. This study offers important implications about the effect of problem-solving self-appraisal on lifelong learning disposition. According to the findings, individuals with high problem-solving self-evaluation are more inclined toward lifelong learning.